REPRESENTASI SOSIAL TENTANG MAKNA MALU PADA GENERASI MUDA DI JAKARTA - Giawa, E. Constant; Nurrachman, Nani (Jurnal Psikologi, 2018)
This study aims to find out the meaning of shame in the young generation of Jakarta. Shame as one of the basic emotions, continues to evolve according to the age level and social changes that occur. The theory used is social representation theory with approach of social representation structure that will find central core and peripheral element of shame. This study used mixed method design: quantitative method with hierarchized evocation technique and qualitative method by conducting interview. The hierarchized evocation technique was performed on 252 participants using a questionnaire. While interviews were conducted on 13 participants which explore further about the shame. Participants were obtained by using snowball and accidental sampling technique, with the criteria as followed: students, at least fifth semester and maximum age is 25. The results show that the meaning of shame in Jakarta young generation is related to self-doubt, events that lead to negative judgment, unideal physical appearance, violation of moral principles and mismatch on etiquette. These five attributes are very strongly attached to the collective memory of the younger generation.